Industrial Policy in the Conditions of External Challenges: a Look from Saint-Petersburg - Yury Vasilyevich Kosov (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article is dedicated to very actual problem of industrial policy of St. Petersburg, region of the Russian Federation. The authors consider questions of development of regional industry, difficulties of investments, decisions of original powers (government and Legislative assembly), cooperation with investors in the field, investment climate, relations with China etc.